PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 4 PARIAMAN - Rahmi, Dwi Indah Gusti; Ratna, Ellya; Nursaid, Nursaid (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is three. First, describing fable text writing skills of class VII students of SMP Negeri 4 Pariaman before using discovery learning models. Secondly, describing fable text writing skills of class VII students of SMP Negeri 4 Pariaman after using discovery learning models. Third, analyze the influence of the use of discovery learning models on fable text writing skills of class VII students of SMP Negeri 4 Pariaman. this type of research is quantitative research with experimental methods. The design of this study was the design of one group pretest and posttest. The population of this study was the seventh grade students of SMP Negeri 4 Pariaman which amounted to 184 people scattered in six classes. The data of this study is the score of the results of the fable text writing skills test before and after using the discovery learning model. the instrument of this research is the performance test. The results of this study are three, namely as follows. First, fable text writing skills before using the discovery learning model, class VII students of SMP Negeri 4 Pariaman are in a sufficient qualification (C) with an average value of 58.18. Second, fable text writing skills after using the discovery learning model, class VII students of SMP Negeri 4 Pariaman are in the qualification of More Than Enough (LdC) with an average value of 68.60. Third, based on the t-test at the level of 0.95 obtained tcount> t table (2.90> 1.70). Based on the results of the study, it was concluded that the discovery learning model can be used as a model problem in learning to write fable text.Â Kata kunci: Pengaruh, Discovery Learning, Teks fabel